BASKETBAL AS AN ALTERNATIVE METHOD TO LEARN SOCIAL COMPETENCE - Putro, Baskoro Nugroho (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2020)
Basketball is a sport that is quite popular in Indonesia. Many schools accommodate the interests and talents of student at basketball in extracurricular activities. Like other sports, basketball has positive values that can be learned. In line with the social competencies established by the Ministry of Education and Culture, Basketball can be used to help achieve these competencies. This study involved 339 individuals from various backgrounds. Individuals that involved in research have experience in basketball as students, athletes, teachers, coaches, parent athletes, and supporters. The purpose of this study is to find out whether basketball has the potential to help students achieve social competence. The approach used in this research is qualitative and quantitative. The results of the research show that statistically, basketball has a strong correlation with social competence, whereas from theoretical studies the characteristics of basketball can support the achievement of social competence.Â Bolabasket adalah olahraga yang cukup populer di Indonesia. Beberapa sekolah mengakomodir minat dan bakat peserta didik dalam bolabasket dengan kegiatan ekstrakurikuler. Seperti olahraga lainnya, bolabasket memiliki nilai positif yang dapat dipelajari. Sejalan dengan kompetensi sosial yang ditetapkan oleh menteri pendidikan dan kebudayaan, bolabasket dapat digunakan untuk mencapai kompetensi tersebut. Dalam penelitian ini melibatkan 339 subjek penelitian dari berbagai latar belakang. Individu yang terlibat dalam penelitian ini memiliki pengalaman dalam bolabasket sebagai siswa, atlet, guru, pelatih, orang tua dan suporter. Tujuan dari penelitian ini adalah untuk mengetahui apakah bolabasket memilik potensi untuk membantu siswa dalam mencapai kompetensi sosial. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif dan kuantitatif. Hasil dari penelitian secara statistik menunjukan, bolabasker memiliki korelasi yang kuat dengan kompetensi sosial, dimana berdasarkan studi literature menunjukkan juga bahwa karakteristik bolabasket dapat mendukung pencapaian kompetensi sosial.